The Brown Alga Padina australis Total Extract and Depressive-like Behavior Following BCG Inoculation in Mice - Afsaneh Yegdaneh; Azadeh Mesripour; Mehrnaz Iravani (Mazandaran University of Medical Sciences, 2023)
Background: Depression is an important psychological disorder because it is a common mental illness that leads to morbidity and suicide. Although appropriate antidepressant drugs exist, they usually have unpleasant side effects and delayed onset.  Objectives: Introducing new compounds such as medicinal plants and oceanic living organisms such as alga is appropriate. Here the depressive-like effects of Padina australis Hauck total extract (PAE) were evaluated following depression induced by Bacillus Calmette-Guérin (BCG) in mice. Methods: Male NMRI mice (average weight: 27±2 g) were used. A single BCG 0.2 mL/mouse was inoculated. PAE effective dose (40 mg/kg) and imipramine (10 mg/kg) were administered as the reference drug for 14 days. The control animals received normal saline. All treatments were administered intraperitoneally. After evaluating the locomotor activity, different depression criteria were assessed by forced swimming test (FST), sucrose preference (SP) test, and novelty-suppressed feeding test (NSFT). Results: Depression was induced by BCG. The selected PAE dose did not cause a significant change in the locomotor activity compared with the control (139±16.9 count), while the immobility time in FST reduced (45.1±11.4 s vs BCG, P<0.001). During the NSFT, the latency decreased (94.7±18.5 s vs BCG, P=0.0365), food intake increased (17.4±2.11 mg/g body weight vs BCG, P=0.023), and SP up to 79.3±4.7%. These changes were similar to imipramine.  Conclusion: PAE showed antidepressant-like effects as despair behavior reduced during FST. Based on NSFT, the stress declined, and animal appetite increased, while SP revealed remission of anhedonia. Further studies are suggested regarding the antidepressant effects of PAE different partitions.